If it's not what You are looking for type in the equation solver your own equation and let us solve it.
t in (-oo:+oo)
-((2/7)*t)-1/7 = -17/49 // + -17/49
-((2/7)*t)-1/7-(-17/49) = 0
(-2/7)*t-1/7+17/49 = 0
10/49-2/7*t = 0 // - 10/49
-2/7*t = -10/49 // : -2/7
t = -10/49/(-2/7)
t = 5/7
t = 5/7
| 6m-2=4 | | -1/2-2n=-37/2 | | 5/6n+5/9=80/63 | | 4+4/5k=36/5 | | t+2/9=68/63 | | -k+3=11/5 | | 5/9-5w=-310/9 | | 7d+8/9=134/9 | | 3/4m+5/6=73/12 | | 2/5+2/7m=62/105 | | -1-2/7w=-71/63 | | -7a-9=-46/9 | | x-2=-8/5 | | t+4=-3 | | x+1/5=11/10 | | k/2=-1/5 | | x+3/7=62/63 | | 5d=15 | | 9=d-1 | | a+1/4=49/4 | | x+2=7/5 | | m+3=8 | | m+7=75/11 | | 2n=1/4 | | a+6=13 | | d+6/7=-43/7 | | a-1/2=-1 | | n/4=5/6 | | t-9=-69/8 | | -1/7=m-1 | | b+7=16 | | k/6=4 |